2017
DOI: 10.1164/rccm.201610-2035ci
|View full text |Cite|
|
Sign up to set email alerts
|

FiftyYearsofResearchinARDS.Setting Positive End-Expiratory Pressure in Acute Respiratory Distress Syndrome

Abstract: Positive end-expiratory pressure (PEEP) has been used during mechanical ventilation since the first description of acute respiratory distress syndrome (ARDS). In the subsequent decades, many different strategies for optimally titrating PEEP have been proposed. Higher PEEP can improve arterial oxygenation, reduce tidal lung stress and strain, and promote more homogenous ventilation by preventing alveolar collapse at end expiration. However, PEEP may also cause circulatory depression and contribute to ventilator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(148 citation statements)
references
References 80 publications
(87 reference statements)
2
137
0
5
Order By: Relevance
“…Allbarello et al reported decreased normal lung volume in COVID-19 pneumonia patients with acute respiratory distress syndrome (ARDS) [9]. We believe this volume loss resulted due to alveolar collapse, which is commonly seen in ARDS [10].…”
Section: Discussionmentioning
confidence: 77%
“…Allbarello et al reported decreased normal lung volume in COVID-19 pneumonia patients with acute respiratory distress syndrome (ARDS) [9]. We believe this volume loss resulted due to alveolar collapse, which is commonly seen in ARDS [10].…”
Section: Discussionmentioning
confidence: 77%
“…In ARDS, lung protection is provided using low tidal volumes, low plateau transpulmonary and driving pressures, but also a positive end-expiratory pressure (PEEP) level sufficient to maintain oxygenation while preventing the opening-closing of alveolar units causing shear stress throughout the respiratory cycle [20]. Clinical trials in ARDS investigated the effect of an open lung strategy, namely involving the use of PEEP levels higher than those strictly required to maintain acceptable oxygenation [21], often in conjunction with recruitment maneuvers to maximize lung aeration [22].…”
Section: Effects Of Peep In Ae-ildmentioning
confidence: 99%
“…While several independent risk factors for development of ARDS have been identified, such as pneumonia, non‐pulmonary‐sepsis or severe injuries, the molecular events leading to ARDS remain poorly understood . Thus, therapeutic options are currently limited to lung‐protective ventilation strategies . Pharmacological interventions that may attenuate progression of mild ARDS to moderate or severe ARDS are currently not available, but urgently needed.…”
Section: Introductionmentioning
confidence: 99%